Innovating Islamic Religious Education through Digital Learning in the Era of Society 5.0 - Mumtahana, Lusia; Ahadiyah, Wahyuni; Elnakep, Mohamed (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study aims to explore in depth the forms and impacts of digital-based innovations in Islamic Religious Education to address the challenges and opportunities of the Society 5.0 era. Within the context of educational transformation that increasingly emphasizes the integration of intelligent technologies Islamic Religious Education is expected not only to be materially relevant but also to adapt to digital developments while remaining grounded in Islamic values. The research method employed is library research with a descriptive qualitative approach, analyzing data from various scholarly sources, nationally accredited journals (Sinta), international publications (Scopus), and policy reports on digital education. The findings reveal that the implementation of digital classrooms through the use of Learning Management Systems (LMS), digital whiteboards, and online libraries significantly enhances students' critical thinking, higher order problem-solving skills (HOTS), and life skills. Furthermore, digital innovation also encompasses the digital management of madrasahs, the development of AI based Islamic applications, and the integration of Islamic digital ethics. The success of these innovations heavily relies on infrastructure readiness, teachers’ digital and pedagogical competence, and a curriculum that harmoniously blends spirituality with technological advancement. This study recommends a holistic and sustainable digital PAI learning model to cultivate adaptive, religious, and highly competitive Muslim generations in the era of the Society 5.0 human centred technological revolution.